Research Models and Gene Augmentation Therapy for CRB1 Retinal Dystrophies - Boon, Nanda; Wijnholds, Jan; Pellissier, Lucie P. (Frontiers in Neuroscience, 2020)
Retinitis pigmentosa (RP) and Leber congenital amaurosis (LCA) are inherited degenerative retinal dystrophies with vision loss that ultimately lead to blindness. Several genes have been shown to be involved in early onset retinal dystrophies, including CRB1 and RPE65. Gene therapy recently became available for young RP patients with variations in the RPE65 gene. Current research programs test adeno-associated viral gene augmentation or editing therapy vectors on various disease models mimicking the disease in patients. These include several animal and emerging human-derived models, such as human induced pluripotent stem cell (hiPSC) derived retinal organoids or hiPSC-derived retinal pigment epithelium, and human donor retinal explants. Variations in the CRB1 gene are a major cause for early onset autosomal recessive RP with patients suffering from visual impairment before their adolescence and for LCA with newborns experiencing severe visual impairment within the first months of life. These patients cannot benefit yet from an available gene therapy treatment. In this review, we will discuss the recent advances, advantages and disadvantages of different CRB1 human and animal retinal degeneration models. In addition, we will describe novel therapeutic tools that have been developed, which could potentially be used for retinal gene augmentation therapy for RP patients with variations in the CRB1 gene.